2012
DOI: 10.1038/jp.2012.32
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study of experiences and needs of 111 fathers of very low birth weight infants in a neonatal intensive care unit

Abstract: Bedside support of fathers, accomplished by the NICU team, could be complemented by additional father-specific non-bedside support, such as peer-education measures or interactive mass media.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 32 publications
(30 reference statements)
4
44
0
Order By: Relevance
“…Consistent with literature we found that mothers and fathers tend to gather information as fathers spend less time at their baby's bedside and miss opportunities to interact with clinical staff therefore receiving “second‐hand” information from their partner. Importantly, German fathers rated any primary interaction with clinical staff very highly (Garten, Nazary, Metze, & Buhrer, ). Danish nurses have implemented strategies to improve communication with parents and have noted early positive outcomes (Weis, Zoffmann, & Egerod,).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with literature we found that mothers and fathers tend to gather information as fathers spend less time at their baby's bedside and miss opportunities to interact with clinical staff therefore receiving “second‐hand” information from their partner. Importantly, German fathers rated any primary interaction with clinical staff very highly (Garten, Nazary, Metze, & Buhrer, ). Danish nurses have implemented strategies to improve communication with parents and have noted early positive outcomes (Weis, Zoffmann, & Egerod,).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to mothers, also fathers of preterm babies have to cope with increased stress levels, emotional exhaustion and difficulties in transitioning into fatherhood (Garten, Nazary, Metze, & Bührer, 2013;Sloan, Rowe, & Jones, 2008). Fathers also go through particular challenges in the NICU.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a pilot study by Garten et al 30 concluded that bedside support could be complemented by father-specific baby care courses, workshops, and peer education as an added benefit for all. The fathers also did not have the benefit of parent-to-parent support to enhance coping.…”
Section: Ongoing Program Developmentmentioning
confidence: 99%